2004
DOI: 10.1111/j.1523-1755.2004.00641.x
|View full text |Cite
|
Sign up to set email alerts
|

Matrilysin (MMP-7) expression in renal tubular damage: Association with Wnt4

Abstract: These observations suggest that matrilysin may have a role in renal tubular injury and progression of tubulointerstitial fibrosis, and that Wnt4 may regulate matrilysin expression in the kidney.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
87
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(92 citation statements)
references
References 43 publications
3
87
0
2
Order By: Relevance
“…A recent study demonstrated the striking down-regulation of REIC͞Dkk-3 in 15 of 17 (88%) RCC tumor samples (49). Like HGF, Wnt family members are normally expressed in kidney during development and in adulthood (19,31,50). Our results suggest that loss of this potential Wnt inhibitor combined with the frequent loss of VHL function in RCC could contribute significantly to tumorigenesis, invasion, and metastasis.…”
Section: Discussionmentioning
confidence: 77%
“…A recent study demonstrated the striking down-regulation of REIC͞Dkk-3 in 15 of 17 (88%) RCC tumor samples (49). Like HGF, Wnt family members are normally expressed in kidney during development and in adulthood (19,31,50). Our results suggest that loss of this potential Wnt inhibitor combined with the frequent loss of VHL function in RCC could contribute significantly to tumorigenesis, invasion, and metastasis.…”
Section: Discussionmentioning
confidence: 77%
“…Notably, MMP-7 was the only MMP significantly upregulated in the liver of biliary atresia in these two studies. Besides the role in pulmonary fibrosis mentioned above, MMP-7 has also been found to be related to progression of tubulointerstitial fibrosis in renal tubular injury in human, 39 and to be involved in the tissue remodeling process and fibrosis of the left atria during progression of heart failure in rat. 40 Furthermore, Lichtinghagen et al 17 analyzed hepatic mRNA expression and reported that MMP-2, MMP-7, and TIMP-1 provided the best discrimination between cirrhosis and pre-cirrhotic stages in patients with chronic active hepatitis C, and steadily increasing mRNA expression with disease progression in MMP-1, -2, -7 and -14 closely correlated to the parameters of fibrogenesis in hepatitis C virus-induced liver cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 As for the kidney, an earlier study documented an increased expression of MMP-7 in polycystic kidney disease, acute kidney injury induced by folic acid, and obstructive nephropathy. 14 However, what regulates MMP-7 expression in diseased kidneys in vivo remains enigmatic. Furthermore, little is known about the relevance of MMP-7 regulation to the progression of renal fibrotic lesions in CKDs.…”
mentioning
confidence: 99%